Electronic Cigarettes: Health Risks and Workplace Policy. (September 2014) - Phillips, Jennan A.
Electronic cigarettes are advertised as "harmless" replacements for tobacco use. Reports of adverse public health outcomes suggest regulatory restrictions over electronic cigarette manufacturing, marketing, and use are needed along with research to determine their health effects.